Green Design of Poly(m-Phenylene Isophthalamide)-Based Thin-Film Composite Membranes for Organic Solvent Nanofiltration and Concentrating Lecithin in Hexane - HUA DAN (American Chemical Society, 2020)
10.1021/acssuschemeng.8b02021